(untitled) (Altre Modernità, 2011)
The paper focuses on My City of Ruins, the song that Bruce Springsteen sang—ten days after the 09/11 terrorist attacks—for "America: A Tribute to Heroes" and that was released in the concept album The Rising in 2002. The essay aims to highlight how the song describes the post 09/11 New York City by opposing the themes of “ruins” and “utopia.” From a textual and musical point of view, My City of Ruins is, in fact, composed of a double structure that balances different feelings: the fear, pain, and loneliness of the victims, in the rock-blues first section; the faith, love, and hope, in the gospel second part. Furthermore, the paper tries to point out how My City of Ruins no longer describes the symbolic ruins of a foreign past—in line with the nineteenth and twentieth-century American cultural tradition of the Grand Tour—but defines the physical signs of a definitively collapsed “American dream,” which can survive only in a utopian and spiritual “Promised Land.”